2019
DOI: 10.1002/jsde.12357
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Tallow, a Renewable Source for the Production of Biosurfactant by Yarrowia lipolytica MTCC9520, and its Application in Silver Nanoparticle Synthesis

Abstract: The present study is focused on the production of a biosurfactant using Yarrowia lipolytica MTCC 9520 by employing inexpensive lipid waste, chicken tallow from slaughterhouses. Plackett–Burman and Box–Behnken Design analyses were adopted for preliminary screening of medium variables and further optimization. The maximal yield of 4.4 g L−1 of the biosurfactant was obtained from the optimized medium. The highest emulsification activity was found to be 55%, and the surface tension decreased to 37 mN m−1 at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…There are no reports in the literature on the thermal stability of biosurfactants produced by S. cerevisiae. However, using thermal analysis on a biosurfactant produced by the yeast Yarrowia lipolytica MTCC9520, Radha et al (2019) found mass loss greater than 9% at a temperature of approximately 220 • C and 13.73% at a temperature of approximately 337 • C. The DSC analysis of this same biosurfactant revealed crystallization and melting temperatures of 112.48 and 116.80 • C, respectively, which is lower than the melting temperature found for the biosurfactant produced by S. cerevisiae. In a stability study of a rhamnolipid biosurfactant produced by Burkholderia thailandensis, Kourmentza et al (2018) found a similar melting temperature (166.40 • C).…”
Section: Discussionmentioning
confidence: 79%
“…There are no reports in the literature on the thermal stability of biosurfactants produced by S. cerevisiae. However, using thermal analysis on a biosurfactant produced by the yeast Yarrowia lipolytica MTCC9520, Radha et al (2019) found mass loss greater than 9% at a temperature of approximately 220 • C and 13.73% at a temperature of approximately 337 • C. The DSC analysis of this same biosurfactant revealed crystallization and melting temperatures of 112.48 and 116.80 • C, respectively, which is lower than the melting temperature found for the biosurfactant produced by S. cerevisiae. In a stability study of a rhamnolipid biosurfactant produced by Burkholderia thailandensis, Kourmentza et al (2018) found a similar melting temperature (166.40 • C).…”
Section: Discussionmentioning
confidence: 79%
“…LPP produced by Mucor circinelloides also reduce the surface tension (26 mNm −1 ) and the viscosity of motor oil by 98.25%, contributing to potential applications in microbial enhanced oil recovery [ 132 ]. The cationic lipoprotein produced by Yarrowia lipolytica MTCC 9520 was applied as a stabilizing agent in the synthesis of silver nanoparticles, whose action was to prevent the formation of aggregates and facilitate nanoparticles production [ 44 ].…”
Section: Structural Classes Properties and Applicationsmentioning
confidence: 99%
“…In this context, several sources of carbon can be used in culture media such as glucose, sucrose [ 231 ], xylose [ 227 ], inulin [ 131 ], cassava wastewater [ 28 ], cane molasses [ 232 ], soy molasses [ 233 ], glycerol [ 234 ] and hydrolyzates from restaurant food waste [ 235 ]. Additionally, lipid sources, such as refined vegetable oils and residual food frying oils [ 71 , 208 , 230 , 236 ], wastewater from the oil industry [ 186 , 237 ], motor oil [ 151 ] and animal fat [ 44 , 238 ], have also been used. In addition, the carbon source supply directly influenced the chemical composition and surfactant properties of sophorolipids produced when S. bombicola was grown in biodiesel or rapeseed oil, with biodiesel a new esterified sophorolipid structure was produced with lower CMC value and surface tension [ 239 ].…”
Section: New Production Technologiesmentioning
confidence: 99%
“…The use biosurfactants to stabilize silver and gold nanoparticles, even in the absence of conventional chemical agents, has been reported. 17,18 In paint and leather processing industries, biosurfactants can be used for the solubilization and removal of components. 19,20 The sector in which these products have been expanding more intensely in recent years is the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactants also play a significant role in other, less common fields. The use biosurfactants to stabilize silver and gold nanoparticles, even in the absence of conventional chemical agents, has been reported 17,18 . In paint and leather processing industries, biosurfactants can be used for the solubilization and removal of components 19,20 …”
Section: Introductionmentioning
confidence: 99%